Translation, Adaptation, and Pilot of a Guided Selfhelp Intervention to Reduce Psychological Distress in South Sudanese Refugees in Uganda - Tol. A.W, Augustinavicius J., Adaku A., Leku R.M., García-Moreno C., van Ommeren M. (Global Mental Health, 2018)
In this period of unprecedented levels of displacement, scalable interventions are needed to address mental health concerns of forced migrants in low-resource settings. This paper describes the adaptation and piloting of a guided, multi-media, self-help intervention, Self-Help Plus (SH+), which was developed to reduce psychological distress in large groups of people affected by adversity. Using a phased approach that included community consultations, cognitive interviewing, facilitator training, pilot implementation, and a qualitative process evaluation, we adapted SH+ for use among South Sudanese refugees in a refugee settlement in northern Uganda.